Mechanisms and traditional Chinese medicine therapeutics for primary osteoporosis: an integrated perspective - An, Zhongcheng; Wu, Bing; Mao, Wangnan; Wu, Lianguo (Frontiers in Endocrinology, 2025)
Primary osteoporosis (POP) is a systemic skeletal disorder characterized by compromised bone microarchitecture. With the progression of population aging trends, POP has garnered increasing societal concern as a major public health challenge. Contemporary research reveals that POP pathogenesis involves intricate interactions among endocrine regulation, genetic predisposition, and neuromodulation pathways. Recent advances in Traditional Chinese Medicine (TCM) investigations have demonstrated its unique therapeutic advantages in POP management through multi-target regulatory mechanisms. This review systematically examines the molecular pathogenesis of POP and deciphers potential therapeutic mechanisms of TCM for POP involving bone metabolism regulation, including herbal compound-induced osteoblast activation, osteoclast inhibition, and extracellular matrix remodeling. By integrating evidence from pharmacokinetic studies and clinical trials, this analysis provides scientific validation for the efficacy and pharmacological rationale of TCM interventions, while proposing novel clinical intervention strategies that synergize traditional therapeutic wisdom with modern precision medicine approaches. This comprehensive review was conducted based on a systematic literature search across PubMed, Web of Science, China National Knowledge Infrastructure (CNKI), and Wanfang Data databases, encompassing original research articles and reviews published between 2004 and 2024. The search focused on the pathogenesis of primary POP (including hormonal regulation, genetic factors, neuromodulation) and the therapeutic effects of Traditional Chinese Medicine (TCM) (single herbs and formulas). Studies were selected according to predefined inclusion (clear relevance, robust methodology) and exclusion criteria (case reports, duplicates, low-quality studies). Key findings from the included literature were synthesized and critically analyzed.